A sustainability assessment system for Chinese iron and steel firms. (1st July 2016) - Long, Yunguang; Pan, Jieyi; Farooq, Sami; Boer, Harry
Abstract: The environmental impact of the Chinese iron and steel industry is huge due to its high consumption of ore, coal and energy, and water and air pollution. It is important not only for China but also for the rest of the world that the Chinese iron and steel industry becomes more sustainable. A sustainable assessment indicator system is an important tool to support that development. Currently, however, a sustainable assessment system, specifically designed to match the characteristics of Chinese iron and steel firms, is not available. In this paper such a system is proposed and evaluated using data from financial and sustainability reports of four leading Chinese iron and steel firms. The proposed sustainable assessment system is envisaged to help Chinese iron and steel firms to objectively investigate their sustainability performance, provide clear and effective information to decision makers, and support the Chinese iron and steel firms' sustainable development. Highlights: The importance of the Chinese iron and steel (IS) industry is emphasized. Chinese IS firms have started to address the sustainability issue but need support. A sustainability assessment (SA) system is developed for Chinese IS firms. The SA system is developed using analytic hierarchy process and an expert survey. The developed SA system is evaluated using data from four Chinese IS firms.